An Empirical Study on the Improvement of R&D Competition Policy for the National R&D Programme. (November 2017) - Hwang, Byung Yong; Suh, Jee Hyun; Kim, Dae Cheol
Despite the increase in government spending on R&D in South Korea (hereafter Korea), there have been limits in enhancing the impact and commercialisation of research outcomes. A new approach to the current mode of R&D is considered necessary to tackle this problem. In 2014, Korea implemented a new competition policy on national R&D by designating six R&D programmes from four different government departments as Competition-type R&D. The purpose of this study is to examine the actual conditions for adoption and to further promote early establishment and wide implementation of the new competition policy on national R&D, and identify the ways for improvement. In this study, we have approached the case with a life-cycle perspective of plan–management–evaluation of R&D. Multiple sources of data collection included documents, surveys and unstandardised interviews with the staff members in the government sector organisations and agencies responsible for the national R&D management. Based on the results of the analysis, we bring suggestions on three areas of improvement: (a) materialising suitable projects to enrol in the R&D competition programme; (b) suggesting competition models for each stage of R&D life cycle; and (c) establishing the institutional basis upon which the policy may be widely adopted. Finally, we discuss possible improvements and the limits of this study.